Fungsi Public Relation Lolié Bakes dalam Membangun Reputasi di Media Sosial Instagram - Nikita Eileen; H. H. Daniel Tamburian (Kiwari, 2022)
Lolié Bakes is a brand that is engaged in cakes or breads. The bakery industry in Indonesia is one of lot industry that affected by the Covid-19 pandemic. Seeing the rapid growth of social media, public relations can be useful to reach both existing and new followers. Social media are going more  popular as they provide freedom from traditional editors and guard the media gateway. The purpose of this study is to find out how the Public Relations function of Lolié Bakes in building a reputation on Instagram social media. The methodology used is descriptive qualitative. The theory used in this research is the Public Relations Function to find out how the Public Relations function of Lolié builds reputation. Based on the data that has been obtained can concluded that the implementation of the Public Relations Functions of Internal Relations, publicity, Advertising, press agentry on social media Instagram Lolié Bakes. The results of this study can be seen from the formation of Lolie Bakes' reputation on Instagram Social Media.   Lolié Bakes merupakan salah satu brand yang bergerak di bidang kue atau roti. Industri bakery di Indonesia adalah salah satu dari sekian banyak yang terkena dampak pandemi Covid-19. Melihat pertumbuhan media sosial yang sangat pesat maka public relations dapat bermanfaat untuk meraih pengikut yang ada maupun pengikut baru. Media sosial menjadi populer karena pembuat bebas memberikan dari editor tradisional dan menjaga gerbang media. Tujuan penelitian ini untuk mencari tahu bagaimana fungsi Public Relations Lolié Bakes dalam membangun reputasi di media sosial Instagram. Metodologi yang digunakan adalah kualitatif deskriptif. Teori yang peneliti gunakan adalah Fungsi Public Relation untuk mengetahui bagaimana fungsi Public Relations Lolié dalam membangun reputasi. Berdasarkan data yang telah didapat oleh peneliti, dapat peneliti simpulkan bahwa diterapkannya Fungsi – Fungsi  Public Relation Hubungan Internal , publisitas, advertising, press agentry di media sosial Instagram Lolié Bakes. Hasil penelitian ini terlihat dari terbentuknya reputasi Lolie Bakes di sosial media Instagram.